Evidence that the effector mechanism of skin allograft rejection is antigen-specific. - Rosenberg, A S (1988)
In vivo rejection responses are initiated by specific T-cell recognition of foreign histocompatibility antigens expressed by tissue allografts, but it is not certain if the effector mechanism mediating the actual tissue injury is also antigen-specific. To directly assess the specificity of the effector phase of in vivo rejection responses, we constructed B6 in equilibrium with A/J allophenic mice that are genetic mosaics whose individual cells express either H-2b or H-2a histocompatibility antigens but not both. Trunk skin from B6 in equilibrium with A/J allophenic mice was grafted onto immunoincompetent H-2b nude mice and allowed to heal and regrow hair that was both black and white, reflecting the genetic mosaicism of the allophenic grafts. One month after engraftment, the H-2b nude animals were reconstituted with syngeneic H-2b T cells reactive against H-2a allodeterminants. An obvious rejection response ensued involving antigen-nonspecific inflammatory destruction of the epidermis and complete hair loss. Despite the intensity of the nonspecific inflammatory response, the allophenic skin grafts survived. Importantly, the allophenic grafts regrew hair and the predominant color of that hair was black, providing visual proof that syngeneic B6 melanocytes and hair follicle cells had not been destroyed. Thus, these results demonstrate that although the intense inflammatory component of skin graft rejection responses is capable of damaging superficial epidermal cells nonspecifically, it does not cause rejection of skin allografts. Rather, rejection of skin allografts is mediated by antigen-specific effector T cells that assess individual cells within the dermis of the graft for expression of foreign histocompatibility antigens.